The Effect of Exposure to Microplastic Polyvinyl Chloride (PVC) in Feed on the Growth and Survival of Tilapia (Oreochromis niloticus) - Putrajab, Eka Wawan; Setyono, Bagus Dwi Hari; Alim, Sahrul (Aquaculture Department, University of Mataram, 2024)
The presence of microplastics in the waters is due to plastic garbage that is difficult to decompose. Tilapia that live in the water has a high tolerance for polluted environments, thus making them vulnerable to microplastic contamination. The most common type of microplastic found in water is polyvinyl chloride. The study aims to investigate the effects of microplastic exposure on Tilapia growth and survival. The research plan used a complete random design (CRD) with four treatments and three repetitions. Exposure to microplastics in fish is carried out through feeding, with doses: without microplastic addition; addition of 0.01 mg per 0.75 g of feed; addition of 0.1 mg for 0.75 g of feeding; and addition of 1 mg for every 0.75 grams of feed. The mixed microplastic feed was given three times a day at a dose of 5% of the fish's body weight. Growth and survival data are analyzed using Anova; if there is any real impact, then further testing is done using Duncan. The study's findings showed that adding microplastics to specific weight growth, absolute weight, absolute length, feed conversion ratio, and survival at a dose of 1 mg per 0.75 g of feed was significantly different from treating the animals without adding microplastics. Therefore, we can conclude that a dose of 1 mg per 0.75 g of feed will impact the growth and survival of tilapia.